PENGARUH KEMAMPUAN MANAJERIAL TERHADAP PENURUNAN NILAI GOODWILL (GOODWILL IMPAIRMENT) (Studi Empiris pada Perusahaan Non Keuangan yang terdaftar di Bursa Efek Indonesia tahun 2014-2017) - Silvia Anke Siregar; Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2020)
The objective of this study is to examine the effect of managerial ability with goodwill impairment loss. The loss of goodwill impairment testing is measured by the loss from previous year of goodwill. Managerial ability is measured by finding the value of efficiency of the manager to maximizing the revenue. This study uses secondary data from annual report of non financial companies listed on the Indonesia Stock Exchange for the period 2014-2017. Based on the purposive sampling method, this study obtained 152 observations. The data were analyzed using tobit regression. The result shows that managerial ability has a negative significant effect on the goodwill impairment loss. This result suggests that the lower the managerial ability is, the the higher the possibility of goodwill impairment occurs.